Some determinants of university student mobility in the Andean countries - Fairlie Reinoso, Alan Carsol (Latin American Journal of Trade Policy, 2021)
The article highlights student mobility as an essential’s axis of the internationalization of higher education, also identify the factors that are in favor the flow of higher education students from developing countries to developed countries. Besides, had established main factors that influence the selection of the country destination from Andean’s country students to developed countries are determined. We estimated a gravity model, to find some determinants of this, and the most important are the income in the destination country, the language, and regulatory barriers (taking as a proxy, the index of economic freedom). This suggests that agreements with countries where there is more openness and less regulations, would favors mobility. But it is necessary to identify other obstacles that should be removed, in the agreements between countries or institutions.